Effect of EvidenceBased Education on Nursing Students SelfEfficacy - Hossein Habibzadeh; Nasrin Khajeali; Hamid Reza Khalkhali; Yosof Mohammadpour (Kerman University of Medical Sciences, 2015)
Background & Objective: Clinical efficacy plays an important role in clinical knowledge and skill application One of the ways to increase selfefficacy is using experience and results of clinical research The aim of the present study was to evaluate the impact of evidencebased education on nursing students selfefficacy Methods: This experimental study was conducted on 48 nursing students in their 3rd semester in Urmia University of Medical Sciences Iran The study subjects were selected using convenience sampling and randomly divided into 2 groups of intervention and control (n = 24) Considering the students training in the orthopedic ward the intervention group participants were divided into 8 groups Students in the intervention group were trained in evidencebased education in 2 sessions each lasting 2 hours Selfefficacy was evaluated before and after training in the control and intervention groups using the generalized selfefficacy (GSE) scale Data were analyzed using SPSS software and chisquare ttest MannWhitney test and Wilcoxon test Data were analyzed using confidence interval of 95 ± 2% Results: Of the students 333% were female and 667% male MannWhitney test showed the selfefficacy of the intervention group students to be significantly higher than control group students (P < 0001) No significant differences were observed in the control group Conclusion: Evidencebased education causes greater improvement in selfefficacy in comparison to conventional methods Therefore the use of this method is recommended in clinical education